STRATEGI PENGHIMPUNAN DANA ZAKAT, INFAQ DAN SHODAQOH SELAMA PANDEMI COVID-19 DI LAZISMU KABUPATEN CIREBON - Evi Masliyatu Rofiqoh Evi; Zaenal Aripin; Siti Inaisyah; Dhurotul Mufidah; Achmad Nurjannah (Al Naqdu, 2022)
COVID-19 that occurred in early 2020 had an impact on all community activities, including zakat, infaq and shodaqoh fund-raising institutions. This study aims to determine what strategies are carried out by the zakat, infaq and shodaqoh fund collection institutions LAZISMU Kab. Cirebon in raising funds during the pandemic. It was found that LAZISMU Kab. Cirebon in raising funds is more emphasized on the use of social media such as Facebook, Instagram, Twitter, YouTube and the website lazismukabcirebon.org. From this strategy there is an increase in assets and fund balances seen from the statement of financial position.